The true Heliocopris bucephalus (Fabricius, 1775). Description of a new species and statement of a new synonymy (Coleoptera, Scarabaeidae, Coprini) - (:unkn) unknown (My University, 2022)
Heliocopris ares n. sp. is decribed from India and Sri Lanka and compared to Heliocopris bucephalus (Fabricius, 1775). The distribution of the two species is detailed and a map is produced. The status of the presumed synonyms of Scarabaeus bucephalus Fabricius, 1775, currently Heliocopris bucephalus (Fabricius, 1775) – Copris tmolus Fischer, 1822, and Scarabaeus cristatus De Geer, 1778 – is examined and clarified. Scarabaeus cristatus De Geer, 1778, is a new synonym of Scarabaeus hamadryas Fabricius, 1775, currently Heliocopris hamadryas (Fabricius, 1775), an African species. All treated species are illustrated.
Keywords: African Research